2020
DOI: 10.3389/fvets.2020.00237
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low Pathogenic Avian Influenza Virus Subtype H10N7 in Poultry and Environmental Water Samples During a Clinical Outbreak in Commercial Free-Range Layers, Netherlands 2017

Abstract: Wild birds are the natural reservoir of the avian influenza virus (AIV) and may transmit AIV to poultry via direct contact or indirectly through the environment. In the Netherlands, a clinically suspected free-range layer flock was reported to the veterinary authorities by the farmer. Increased mortality, a decreased feed intake, and a drop in egg production were observed. Subsequently, an infection with low pathogenic avian influenza virus was detected. This study describes the diagnostic procedures used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Another study showed that cats were also highly susceptible to HPAI H5N1 (A/Vietnam/1194/2004) infection after eating virus-infected chicks and demonstrated systemic disease including brain lesions already 7 days after experimental infection [ 28 ]. These findings lead us to the hypothesis that the red foxes, polecats, badger, and otter were infected by eating carcasses; however, ingesting water contaminated with infected bird feces could also be a route of infection [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that cats were also highly susceptible to HPAI H5N1 (A/Vietnam/1194/2004) infection after eating virus-infected chicks and demonstrated systemic disease including brain lesions already 7 days after experimental infection [ 28 ]. These findings lead us to the hypothesis that the red foxes, polecats, badger, and otter were infected by eating carcasses; however, ingesting water contaminated with infected bird feces could also be a route of infection [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suspension was filtered, after the final filtering step (0.2 µM filter, Nalgene) a sample of 5 ml was incubated with 1% of penicillin and gentamycin and incubated at room temperature for 1 h. RNA was isolated using MagNA Pure as described above. For sampling of the water, a 1- l sample was collected and filtered directly as described previously [ 29 ]. Briefly, the water was filtered using a hydrophilic mixed cellulose esters membrane (MF-Millipore™ Membrane Filter, Merck).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was isolated using MagNA Pure as described above. For sampling of the water, a 1 liter sample was collected and filtered directly as described previously 29 . Briefly, the water was filtered using a hydrophilic mixed cellulose esters membrane (MF-Millipore™ Membrane Filter, Merck).…”
Section: Virus Detection In Bedding and Watermentioning
confidence: 99%
“…This might provide a clue for minimal chances of viral spread from apparently healthy rural poultry birds through oral route. The association between migratory birds, backyard poultry and the current status on avian influenza has been investigated in many countries like in Europe and UK (Hansen et al, 2018), in China (Wang et al, 2018) and in Netherlands (Germeraad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%